Molecular Effects of Biogenic Zinc Nanoparticles on the Growth and Development of Brassica napus L. Revealed by Proteomics and Transcriptomics - Sohail; Sawati, Laraib; Ferrari, Elenora; Stierhof, York-Dieter; Kemmerling, Birgit; Mashwani, Zia-ur-Rehman (Frontiers in Plant Science, 2022)
The present study was aimed to reveal the molecular responses of Brassica plants to photosynthesized zinc nanoparticles. Zinc nanoparticles (Zn NPs) were synthesized by using Mentha arvensis aqueous extracts followed by their morphological and optical evaluation using various material characterization techniques such as UV-Visible Spectrophotometry, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD). The morphological evaluation showed that the Zn NPs are irregularly shaped, showing aggregation while the average size of a single particle was ~30 nm. The nanoparticles were observed crystalline by using XRD. The foliar applications of various concentrations of biogenic Zn NPs were used to study their effects on the growth and development of the Brassica napus L verities (Faisal canola and Shiralee). It was observed experimentally that the 15 mg/L of Zn NPs have significantly improved chlorophyll and carotenoid contents in Brassica napus varieties. The biomass accumulation was also improved on exposure to Zn NPs. The proteomic profiling revealed proteins involved in photosynthesis, transport, glycolysis, and stress response. These alterations were observed in both tested Brassica varieties. On exposure to Zn NPs differential expression of genes of Brassica napus var. Faisal was observed being involved in Photosynthesis, Structural constituent of the ribosome, and oxidative stress response. In the Brassica var. Shiralee was seen. The results of the present study show that foliar applications of biogenic Zn NPs alter the transcriptome and protein resulting in improving growth and development of the plant.